2014
DOI: 10.1038/srep06180
|View full text |Cite
|
Sign up to set email alerts
|

Effective charge separation in the rutile TiO2 nanorod-coupled α-Fe2O3 with exceptionally high visible activities

Abstract: Herein, we have fabricated rutile TiO2 nanorod-coupled α-Fe2O3 by a wet-chemical process. It is demonstrated that the visible activities for photoelectrochemical water oxidation and for degrading pollutant of α-Fe2O3 are greatly enhanced after coupling a proper amount of rutile nanorods. The enhanced activity is attributed to the prolonged lifetime and improved separation of photogenerated charges mainly by the transient surface photovoltage responses. Interestingly, the observed EPR signals (with g⊥ = 1.963 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 46 publications
2
88
0
Order By: Relevance
“…It can be seen clearly, that the fluorescence peaks intensity gradually increases with increase in amount of TiO 2 coupled, and the strongest fluorescence peak intensity is observed for 9T/P-BFO nanocomposite. Therefore, it is suggested that the enhanced visible-light photocatalytic activities of T/P-BFO nanocomposites for acetaldehyde and phenol degradation are mainly attributed to the significant increase in amount of OH -radicals produced [19,32].…”
Section: Discussion On Mechanismmentioning
confidence: 99%
“…It can be seen clearly, that the fluorescence peaks intensity gradually increases with increase in amount of TiO 2 coupled, and the strongest fluorescence peak intensity is observed for 9T/P-BFO nanocomposite. Therefore, it is suggested that the enhanced visible-light photocatalytic activities of T/P-BFO nanocomposites for acetaldehyde and phenol degradation are mainly attributed to the significant increase in amount of OH -radicals produced [19,32].…”
Section: Discussion On Mechanismmentioning
confidence: 99%
“…6,31 However, by applying electrochemical impedance spectroscopy, PEC and electron paramagnetic resonance studies, Luan et al evidently confirmed the occurrence of an uncommon transfer of visible-excited high-energy electrons from hematite to rutile TiO 2 . 32 It was suggested that in this process, the excited electrons in hematite populate different energy levels and while low energy electrons recombine with VB holes, high-energy electrons transfer to the CB of rutile. 6,32 Such uncommon electron transfer, leading to improved charge separation and enhanced PEC properties, was also observed in BiVO 3 -ZnO heterojunction photoanodes 33 and recently also for BiVO 3 -TiO 2 heterojunction photoanodes.…”
Section: Considering That the Structural And Chemical Investigation Smentioning
confidence: 99%
“…32 It was suggested that in this process, the excited electrons in hematite populate different energy levels and while low energy electrons recombine with VB holes, high-energy electrons transfer to the CB of rutile. 6,32 Such uncommon electron transfer, leading to improved charge separation and enhanced PEC properties, was also observed in BiVO 3 -ZnO heterojunction photoanodes 33 and recently also for BiVO 3 -TiO 2 heterojunction photoanodes. 6,34,35 In addition, the high efficiency could as well be explained on the basis of the formation of a rutile blocking layer.…”
Section: Considering That the Structural And Chemical Investigation Smentioning
confidence: 99%
“…The photoelectrodes were illuminated with a 500 W Xenon lamp to produce a visible light source with an intensity of 64 mW/cm 2 after utilizing a filter to remove light below the wavelength of 420 nm [15]. The steady-state surface photovoltage spectra (SS-SPS) instrument was a home-built apparatus as discussed elsewhere [20].…”
Section: Materials Characterization and Activity Evaluationmentioning
confidence: 99%
“…Based on our previous works [14,15], narrow band-gap semiconductors with low conduction band (CB) could be excited by visible light with energy higher than their band-gaps, hence the electrons in the valence band (VB) will be excited to the high energy level over bottom of the CB (high energy electrons). These high energy electrons could be transferred thermodynamically to the CB of another semiconductor.…”
Section: Introductionmentioning
confidence: 99%